Penerapan Pendekatan Scientific Dengan Model Pembelajaran Problem Based Intruction Dan Discovery Learning Ditinjau Dari Komunikasi Matematika Siswa - Rizky Hidayat, Hermawan; , Dra. N.Setyaningsih, M.Si (2017)
The goal of research to describe and analyze: (1) the influence of scientific approach with a model of learning Problem Based Learning and Discovery Intruction towards achievement of learning math. (2) the influence of mathematical communication students who are categorized in levels of high, medium and low towards the achievements of the student learning. (3) the interaction between the scientific approach with a model of learning Problem Based Instruction and Discovery Learning and communications student achievement against learning math. This research is a research experiment with quasi experimental design. The population in this research is the entire class X students semester even SMK Muhammadiyah Kartasura academic year 2015/2016 which consists of 6 classes, namely, Sampling techniques using cluster random sampling. Data collection method using tests and documentation. Data analysis techniques using variansi analysis of two lines with the same cells. The results of data analysis with a 5% significance level obtained: (1) there are influences between the learning model with the Scientific approach to Problem Based Learning and Discovery Intruction towards achievement of learning math, with F_A = 10,173 (2) there is the influence of the ability to communicate mathematics toward mathematical learning achievement, with 6.298 = F_B (3) there is no interaction between strategy between the Scientific approach with a model of learning Problem Based Learning and Discovery Intruction of the ability to communicate mathematics student achievement against learning math with F AB = 0,572. Keyword: Problem Based Intruction. Discovery Learning. Communication Of Mathematics. Achievements Of Learning Math.